End-binding E3 ubiquitin ligases enable protease signaling - Ravalin, Matthew (ACS Chem Biol, 2019)
Post-translational modifications (PTMs) direct the assembly of protein complexes. In this context, proteolysis is a unique PTM because it is irreversible; the hydrolysis of the peptide backbone generates separate fragments bearing a new N and C terminus. Proteolysis can “re-wire” protein-protein interactions (PPIs) via the recruitment of end-binding proteins to new termini. In this review, we focus on the role of proteolysis in specifically creating complexes by recruiting E3 ubiquitin ligases to new N and C termini. These complexes potentiate proteolytic signaling by “erasing” proteolytic modifications. This activity tunes the duration and magnitude of protease signaling events. Recent work has shown that the stepwise process of proteolysis, end-binding by E3 ubiquitin ligases, and fragment turnover is associated with both the nascent N terminus (i.e. N-degron pathways) and the nascent C terminus (i.e. the C-degron pathways). Here, we discuss how these pathways might harmonize protease signaling with protein homeostasis (i.e. proteostasis).